Assessment of skills development in a residency research track for internal medicine residents - Martin, Gabrielle; Tran, Brittany; Denu, Mawulorm; Mackey, Katherine; O’Connor, Mark J.; Epstein, Mara M.; Fitzgibbons, Timothy; Kovell, Lara (International Journal of Educational Technology and Learning, 2025)
There has been minimal formal evaluation of residency research programs. This study was designed to assess the impact of an internal medicine residency research track on residents’ confidence and attitudes about research skills. In 2022, a research track was started within the UMass Chan internal medicine residency. Ten residents (five PGY-2 and five PGY-3) were selected to participate. Pre- and post-program surveys were created distributed electronically at baseline and one year, with 100% response rate. Survey questions, ranked on a Likert scale (1–5), assessed residents' confidence and self-perceived importance of research skills. Change scores were utilized to compare post-survey responses to baseline using paired t-tests. At baseline, residents reported mean (SD) 5.8 (5.7) publications, which increased by 1.4 (1.8) in one year (p = 0.02). IRB submission, conducting basic analyses, and grant writing had the lowest baseline scores. After one-year, mean confidence scores significantly increased for writing study protocols (pre-score (SD): 3.0 (1.2), Δ: 0.6), IRB submissions (2.6 (1.1), Δ: 0.9), designing survey questions (2.9 (1.3), Δ: 0.9), writing methods (3.4 (1.0), Δ: 0.5), and designing blank tables (3.4 (1.5), Δ: 0.4, all p < 0.05). No significant score reductions were noted. Implementation of research tracks can improve research skills and overcome some barriers to research during residency training. Our study demonstrates improved confidence in research skills through completion of research didactics and close mentorship. Future curricula should conduct needs assessments and provide an individualized approach to maintain research scholarship during residency.